Neoproterozoic S-type granites in the Alxa Block, westernmost North China and tectonic implications: in situ zircon U-Pb-Hf-O isotopic and geochemical constraints - Dan, W.; Li, X.; Wang, Qiang; Wang, Xuan-Ce; Liu, Y. (American Journal of Science, 2014)
The Alxa Block in northern China has been traditionally considered as the westernmost part of the Archean North China Craton (NCC). However, recent studies revealed that there are few Archean rocks exposed in the Alxa Block, and the Paleoproterozoic geology of this block is different from that of the western part of the NCC. Thus, the tectonic affinity of the Alxa Block to the NCC and/or other Precambrian blocks needs further investigations. In this study, we carry out integrated analyses of in situ zircon U–Pb age and Hf–O isotopes as well as whole-rock geochemistry and Nd isotopes for the Neoproterozoic Dabusushan and Naimumaodao granites from central Alxa Block. Secondary ion mass spectrometry (SIMS) U–Pb zircon dating results indicate that the Naimumaodao and Dabusushan granite plutons were formed at ca. 930 Ma and ca. 910 Ma, respectively. These granites are peraluminous (A/CNK value >1.0), and contain peraluminous minerals such as muscovite and tourmaline, similar to those of S-type granites. They are characterized by high zircon δ18O values of ca. 8.2 to 12.1 permil, corresponding to a calculated magmatic δ18O value of ca. 10.5 to 14.3 permil, variable zircon εHf(t) values of −6.2 to +3.8 (corresponding to Hf model ages of 2.2 to 1.6 Ga) and whole-rock εNd(t) values of −10.1 to −4.5 (corresponding to Nd model ages of 2.4-1.9 Ga). The petrological and Nd–Hf–O isotopic study indicated that these granites were most probably generated by remelting of dominant (meta)sedimentary rocks in an orogenesis-related compressional environment. There is a clear contrast in the Precambrian geological evolution, including basement rock age data, Precambrian magmatism and detrital zircon age patterns, between the Alxa Block and the NCC. Furthermore, the new in-situ detrital zircon ages on Neoproterozoic (meta)sedimentary rock suggest that Alxa Block is likely related to the Cathaysia Block of South China during the Neoproterozoic, and amalgamated with the NCC since the Early Paleozoic. Thus, our new data suggest that the Alxa Block is most likely a separated Precambrian terrane from the Western Block of the NCC.